2017
DOI: 10.1016/j.ijso.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple organ dysfunction syndrome (MODS) prediction score in multi-trauma patients

Abstract: Background Multiple organ dysfunction syndrome (MODS) in patients with major trauma remains a frequent and devastating complication in emergency departments and intensive care units. Easily and accurately identifying patients at risk for MODS post-injury, especially in multi-trauma cases, is important. The aim of this study was to develop an instrument to predict the development of MODS in adult multi-trauma patients using clinical and laboratory data available in the first 24 h after trauma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The ISS predicts further organ failure and patient outcome ( 126 ). MODS incidence can reach 60% of patients ( 127 ).…”
Section: Clinical Consequences: Damp-related Organ Dysfunctionmentioning
confidence: 99%
“…The ISS predicts further organ failure and patient outcome ( 126 ). MODS incidence can reach 60% of patients ( 127 ).…”
Section: Clinical Consequences: Damp-related Organ Dysfunctionmentioning
confidence: 99%
“…Specifically, we have addressed the inadequacies of the current clinical scoring systems used for the assessment of trauma severity, namely New Injury Severity Score (NISS) and Probability of Survival (PS14). They are the main outcome measurements evaluated in TARN (the Trauma Audit and Research Network) and have both shown a high correlation with mortality and length of stay and act as the general predictors for outcomes such as MODS development 14 and sepsis, irrespective of the underlying biological differences of the outcomes. NISS is based on the sum of squares of the Abbreviated Injury Scale (AIS) scores of a patient’s injuries and hence is limited to anatomical information only, whereas PS14 is modelled based on age, gender, Injury Severity Score (ISS), pre-existing medical conditions, patient outcome (up to 30 days) 15 and Glasgow Coma Score (GCS) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative degree of severity was determined using three scores of mortality and morbidity: the Pediatric Risk of Mortality (PRISM) III scoring system, the PELOD-2 score, and the Multiple Organ Dysfunction (MODS) score. 18 19 20…”
Section: Methodsmentioning
confidence: 99%
“…The postoperative degree of severity was determined using three scores of mortality and morbidity: the Pediatric Risk of Mortality (PRISM) III scoring system, the PELOD-2 score, and the Multiple Organ Dysfunction (MODS) score. [18][19][20] We defined surgical complexity using the RACHS-1 score. The RACHS-1 score has been used as a standardized classification tool for cardiac repairs in children younger than 18 years; it is predictive of major adverse events and prolonged lengths of hospitalization stay.…”
Section: Data Collectionmentioning
confidence: 99%